OXIDATION OF ARSENOPYRITE AND DEPOSITION OF GOLD ON THE OXIDIZED SURFACES: A SCANNING PROBE MICROSCOPY, TUNNELING SPECTROSCOPY AND XPS STUDY - Mikhlin Y.L.; Romanchenko A.S.; Asanov I.P. (My University, 2006)
We have used ex situ atomic force microscopy (AFM), scanning tunneling microscopy and spectroscopy (STM/STS) and X-ray photoelectron spectroscopy (XPS) to study the surfaces of natural arsenopyrite samples that were electrochemically polarized in 1 M HCl, or leached in acidic solutions containing ferric iron salts, and then reacted with aqueous gold (III) chloride at ambient temperatures. For arsenopyrite oxidized on a positive-going potential sweep, progressively increasing amounts of surface Fe(III)-O and As-O species, and of S/Fe and S/As ratios in a non-stoichiometric sulfidic layer were found. The products formed in the sweep to a potential of 0.6 V (Ag/AgCl) of the passivity region are shaped in about 100 nm protrusions of two sorts, which are arranged in micrometer-size separate areas, while they are largely mixed at higher, "transpassive" potentials. The quantities of surface alteration substances notably decrease after leaching in ferric chloride and ferric sulfate acidic solutions. Passivation of arsenopyrite was suggested to associate with the disordered, metal-deficient surface layer having moderate excess of sulfur rather than with the products of arsenopyrite oxidation. Exposure of arsenopyrite to 10-5-10-3 M AuCl4- (pH 2) solutions results in the deposition of 8-50 nm gold particles; only a small fraction of the gold is present as Au(I)-S species. The electrochemical oxidation at 0.6 V or ageing of arsenopyrite in air promotes the subsequent gold deposition; in contrast, the amount of Au deposited on arsenopyrite that was treated by leaching in ferric chloride and sulfate solutions was about 10 times smaller than with polished arsenopyrite samples. It has been concluded that reducing agents formed as intermediates of arsenopyrite decomposition facilitate the Au0 cementation although other factors related to the surface state of the arsenopyrite play a role as well. A decrease in the tunneling current magnitudes with decreasing the Au0 particle size has been revealed using STS. This effect along with the increase by 0.2-0.5 eV in the XPS Au 4f binding energies were tentatively ascribed to retarding the electron transitions by emerging electrostatic charge on gold nanoparticles (Coulomb blockade). Possible mechanisms for the effects, and their potential role in the deposition and hydrometallurgy of "invisible" gold are discussed. © 2006 Elsevier Inc. All rights reserved.